2021
DOI: 10.1038/s41598-021-86579-3
|View full text |Cite
|
Sign up to set email alerts
|

Innovative motor and cognitive dual-task approaches combining upper and lower limbs may improve dementia early detection

Abstract: Motor and Cognitive Dual-Task (MCDT) represents an innovative chance to assess Mild Cognitive Impairment (MCI). We compare two novel MCDTs, fore-finger tapping (FTAP), toe-tapping (TTHP), to gold standards for cognitive screening (Mini-Mental State Examination—MMSE), and to a well-established MCDT (GAIT). We administered the aforementioned MCDTs to 44 subjects (MCIs and controls). Motor parameters were extracted, and correlations with MMSE investigated. Logistic regression models were built, and AUC areas comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
1
20
1
Order By: Relevance
“…Our results are consistent with other analyses, which show the association of dualtask tests with cognitive function [20][21][22]. Participants walked the standard TUG for the dual-task animals while subtracting serial 7s from 100 aloud or enumerating animals aloud.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with other analyses, which show the association of dualtask tests with cognitive function [20][21][22]. Participants walked the standard TUG for the dual-task animals while subtracting serial 7s from 100 aloud or enumerating animals aloud.…”
Section: Discussionsupporting
confidence: 91%
“…A total of 155 (62%) cases TUG manual; 23 (9.2%) had cognitive and 72 (28.2%) physical problems while performing tasks. The median score was 16 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) seconds, stride number during the test-23 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28), and while turning around-6 (5)(6)(7)(8). DTC was 11 (0-25)%.…”
Section: Single Task and Dual-task Gait Test Resultsmentioning
confidence: 99%
“…For example, Rosso and colleagues proposed that dual-task walking assessment can be used as a risk assessment tool for mild cognitive impairment (MCI) [ 22 ]. Similarly, Mancioppi and colleagues stated that a dual-task assessment incorporating cognitive and motor tasks is effective for MCI diagnosis [ 23 ]. Finally, de Oliveira Silva and colleagues suggested that poor dual-task gait performance should be considered as a functional screening tool for dementia [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could, consequently, improve the prognosis of a population with access difficulties and give them an opportunity to receive specialized care. Given that there is no sufficient evidence using GS or HS to identify cognitive impairment, many recent publications suggest combining motor and cognitive measures to improve the classification of older adults at risk of dementia (52)(53)(54)(55). So far, studies have reported the usefulness of these motor biomarkers, but there is a little evidence of which specific cognitive domains are related to the motor performance.…”
Section: Discussionmentioning
confidence: 99%